1995
DOI: 10.1042/cs0880651
|View full text |Cite
|
Sign up to set email alerts
|

A New Non-Invasive Statistical Method to Assess the Spontaneous Cardiac Baroreflex in Humans

Abstract: 1. A new method was developed to evaluate cardiac baroreflex sensitivity. The association of a high systolic blood pressure with a low heart rate or the converse is considered to be under the influence of cardiac baroreflex activity. This method is based on the determination of the statistical dependence between systolic blood pressure and heart rate values obtained non-invasively by a Finapres device. Our computerized analysis selects the associations with the highest statistical dependence. A 'Z-coefficient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 0 publications
0
28
0
4
Order By: Relevance
“…3 The determination of BRS in the temporal domain using the sequence method had consistently been reported to be strongly correlated with spectral BRS determination. [15][16][17][18] As in our experience the sequence method appeared to be slightly less reproducible at short term (1 week), we now only determine BRS in the frequency domain. Recently, Johnston et al also reported lower coefficients of variation and reproducibility coefficients if BRS were determined with the spectral method instead of the sequence method.…”
Section: Figure 1 Correlations Between Age and S-brs At Inclusion (Amentioning
confidence: 99%
See 2 more Smart Citations
“…3 The determination of BRS in the temporal domain using the sequence method had consistently been reported to be strongly correlated with spectral BRS determination. [15][16][17][18] As in our experience the sequence method appeared to be slightly less reproducible at short term (1 week), we now only determine BRS in the frequency domain. Recently, Johnston et al also reported lower coefficients of variation and reproducibility coefficients if BRS were determined with the spectral method instead of the sequence method.…”
Section: Figure 1 Correlations Between Age and S-brs At Inclusion (Amentioning
confidence: 99%
“…Because S-BRS is partly derived from SBP determination, any estimate of its time evolution is limited by the time evolution of the BP signal. Because S-BRS is reproducible in the short term 15,[23][24][25] and has a predictable evolution in the long term, S-BRS can be considered an intrinsic characteristic of each subject and therefore used in research studies and clinical practice.…”
Section: Figure 1 Correlations Between Age and S-brs At Inclusion (Amentioning
confidence: 99%
See 1 more Smart Citation
“…A Z-coefficient statistical method has also been proposed [12], but the method needs long recording periods to reliably estimate the required probability functions.…”
Section: A) Time-domain Methodsmentioning
confidence: 99%
“…α HF ). An alternative way to quantify BRS was introduced by Ducher et al [1995], where the relation between SBP values and BBI is assessed statistically. The statistical level of coupling is quantified by the Z-index, which is a function of SBP and BBI.…”
Section: Baroreceptor Sensitivitymentioning
confidence: 99%